1992
DOI: 10.1111/j.1751-1097.1992.tb02218.x
|View full text |Cite
|
Sign up to set email alerts
|

ACTION SPECTRUM FOR ENHANCEMENT OF PHOTOTROPISM BY Arabidopsis thaliana SEEDLINGS

Abstract: Abstract— Fluence‐response relationships have been measured at wavelengths from 350 to 760 nm for the enhancement of phototropism in Arabidopsis thulium L. (Heynh) strain “Estland” by an irradiation at each of these wavelengths, given 2 h prior to a 450 nm inductive unilateral irradiation. Action spectra have been constructed from these fluence‐response relationships based on: (i) the fluence required to obtain a curvature of 25° (corresponding to an enhancement of 15°), (ii) the fluence required to obtain 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Therefore, it is evident that a form of interaction occurs between these two distinct sensory-response systems. Previous studies have shown that enhancement is maximized when the red-light stimulus precedes the blue-light phototropic stimulus by 2 h (Janoudi and Poff, 1991), and it was suggested that phytochrome affects the phototropic response by modulating a component of the blue-light signal transduction sequence (Janoudi and Poff, 1992). It is also possible that the effect of phytochrome on phototropism is indirect.…”
Section: Dlscusslonmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is evident that a form of interaction occurs between these two distinct sensory-response systems. Previous studies have shown that enhancement is maximized when the red-light stimulus precedes the blue-light phototropic stimulus by 2 h (Janoudi and Poff, 1991), and it was suggested that phytochrome affects the phototropic response by modulating a component of the blue-light signal transduction sequence (Janoudi and Poff, 1992). It is also possible that the effect of phytochrome on phototropism is indirect.…”
Section: Dlscusslonmentioning
confidence: 93%
“…F40/CW [General Electric]; 600-700 nm with maximum intensity at 658 nm) given from above 2 h prior to the phototropic stimulus (Janoudi and Poff, 1991). For most experiments, the red-light intensity was saturating for the enhancement response (Janoudi and Poff, 1992). When necessary, the intensity of the red-light treatment was varied by the addition of metal neutral density screens.…”
Section: Phototropism Experimentsmentioning
confidence: 99%
“…The time threshold for second positive curvature is reduced by exposure to red light before unilateral blue light (62). Even in the absence of a red light pulse, the phyA phyB double mutant requires prolonged exposures to blue light (compared to the wild type) to exhibit second positive curvature (58) (Fig.…”
Section: ϫ2mentioning
confidence: 96%
“…A pulse of red light given 2 h before unilateral blue light is perceived by phytochromes and enhances first positive curvature (62). This enhancement is reduced in the phyA and phyB mutants (63,64) and absent in the phyA phyB double mutant (58).…”
Section: ϫ2mentioning
confidence: 99%
“…In general,, R treatments can greatly enhance the phototropic response in primary shoots (Chon & Briggs 1966;Janoudi & Poff 1992;Liu & lino 1996). In Arabidopsis, phytochrome activation by R has been suggested to result in the production of an unknown substance that functions to amplify the phototropic response (Janoudi & Poff 1991).…”
Section: Phytochrome and Phototropismmentioning
confidence: 99%